A method for improving the room temperature mechanical properties of molybdenum-niobium single crystals
By adding niobium elements to the molybdenum single crystal and vacuum annealing, the problem of insufficient strength and high temperature stability of pure molybdenum single crystal is solved, and the mechanical properties of molybdenum niobium single crystal is significantly improved, especially the plastic deformation ability.
Patent Information
- Application Number
- CN202211496675.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-11-25
AI Technical Summary
Pure molybdenum single crystal has better room temperature plasticity but lowers strength, making it difficult to meet the mechanical properties requirements in actual use.
Niobium is added to the molybdenum single crystal and molybdenum niobium single crystal is prepared by smelting in the electron beam suspension area, followed by vacuum annealing to reduce internal stress and promote dislocation slip.
It effectively improves the strength and high temperature stability of molybdenum niobium single crystal, especially the plastic deformation ability, and improves its room temperature mechanical properties.
Smart Images

Figure CN115787063B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optimizing the room temperature mechanical properties of molybdenum-niobium single crystals, and specifically relates to a method for improving the room temperature mechanical properties of molybdenum-niobium single crystals. Background Art
[0002] Metallic molybdenum is a typical body-centered cubic metal with a high melting point (~2610°C) and excellent high-temperature properties, such as high thermal stability and good physical and chemical properties. In addition, among refractory metals, the cost of molybdenum is relatively low. Considering that there are a large number of large-angle grain boundaries in traditional polycrystalline molybdenum, and there are a large number of defects at the grain boundaries. These defects will lead to poor structural stability at high temperatures, such as increased creep rate and segregation of alloy elements to grain boundaries. Therefore, in environments with harsh service conditions, single crystal molybdenum and molybdenum alloys are usually used to replace traditional polycrystalline molybdenum materials. However, the room temperature plasticity of pure molybdenum single crystals is good, but the strength is reduced, which is insufficient in actual use.
[0003] Therefore, it is necessary to provide a molybdenum-niobium single crystal with excellent mechanical properties at room temperature. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for improving the room temperature mechanical properties of molybdenum-niobium single crystals in view of the deficiencies of the above-mentioned prior art. The method effectively improves the strength and high temperature stability of pure molybdenum single crystals by adding the alloying element niobium to the molybdenum single crystals, and vacuum anneals the molybdenum-niobium single crystals prepared by electron beam suspension zone melting, effectively reducing the internal stress of the molybdenum-niobium single crystal system, thereby promoting dislocation slip, thereby improving the mechanical properties of the molybdenum-niobium single crystals, especially the plastic deformation ability.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for improving the room temperature mechanical properties of molybdenum niobium single crystal, characterized in that the method comprises the following steps:
[0006] Step 1: mixing a molybdenum raw material and a niobium raw material, and then performing electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing;
[0007] Step 2: vacuum annealing the single crystal molybdenum-niobium alloy before annealing obtained in step 1 to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties.
[0008] The structural defects, i.e., dislocations, inside the molybdenum-niobium single crystal obtained by electron beam zone melting in the present invention are relatively low, but there are still a large number of subgrain boundaries formed by entanglement of dislocation networks, and due to the addition of alloying elements, additional internal stress is generated near the dislocation line due to the segregation of elements, thereby increasing the potential barrier for dislocation initiation. Therefore, through vacuum annealing, the internal stress of the molybdenum-niobium single crystal system is effectively reduced, thereby promoting dislocation slip, thereby improving the mechanical properties of the molybdenum-niobium single crystal, especially the plastic deformation ability.
[0009] The above-mentioned method for improving the room temperature mechanical properties of molybdenum-niobium single crystals is characterized in that the single crystal molybdenum-niobium alloy in step 1 is a rod-shaped sample with a diameter of 29mm to 31mm and a length of 98mm to 102mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees. The present invention uses a rod-shaped sample for annealing in order to make the sample consistent with the heat conduction direction during the heating and cooling process of the single crystal growth, that is, axially radially outward, and the size is limited to a diameter of 29mm to 31mm and a length of 98mm to 102mm in order to consider the actual use conditions, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is limited to no more than 3 degrees in order to reduce the dispersion of grain orientation and defect density, thereby improving the structural stability of the molybdenum-niobium single crystal.
[0010] The above-mentioned method for improving the room temperature mechanical properties of molybdenum-niobium single crystals is characterized in that the mass content of niobium element in the single crystal molybdenum-niobium alloy in step 1 is 3% to 6%, and the balance is molybdenum.
[0011] The above-mentioned method for improving the room temperature mechanical properties of molybdenum-niobium single crystal is characterized in that the mass content of niobium element in the single crystal molybdenum-niobium alloy is 3%, the balance is molybdenum, and the molecular formula is Mo 97 Nb 3 The mass content of niobium in the single crystal molybdenum-niobium alloy is 6%, the balance is molybdenum, and the molecular formula is Mo 94 Nb 6 The present invention uses Mo 97 Nb 3 Single crystal and Mo 94 Nb 6 Single crystals have significantly better high-temperature strength and structural stability than pure Mo polycrystalline and single crystals, and can be used as core structural components for nuclear power sources.
[0012] The above method for improving the room temperature mechanical properties of molybdenum-niobium single crystals is characterized in that the temperature of the vacuum annealing in step 2 is 1100° C. to 1700° C. The present invention effectively reduces the internal stress of the molybdenum-niobium single crystal system by controlling the temperature of the vacuum annealing, thereby promoting dislocation slip, thereby improving the mechanical properties of the molybdenum-niobium single crystal, especially the plastic deformation ability.
[0013] The above method for improving the room temperature mechanical properties of molybdenum-niobium single crystals is characterized in that when the molecular formula of the single crystal molybdenum-niobium alloy is Mo 97 Nb 3 The annealing temperature is 1485℃~1515℃. When the molecular formula of the single crystal molybdenum-niobium alloy is Mo 94 Nb 6 The annealing temperature is 1285℃~1315℃.
[0014] The present invention is for Mo 97 Nb 3For single crystal, annealing at 1285℃~1315℃ greatly improves the elongation of the alloy, but greatly reduces the yield strength. 97 Nb 3 The optimal annealing temperature for single crystal is 1485℃~1515℃. 94 Nb 6 For single crystal, low temperature annealing at 1085℃~1115℃ and 1285℃~1315℃ can significantly improve the yield strength of the alloy. Annealing at higher temperatures of 1485℃~1515℃ and 1685℃~1715℃ can effectively improve the elongation of the alloy. 94 Nb 6 The optimal annealing temperature for single crystal is 1285℃~1315℃.
[0015] The above method for improving the room temperature mechanical properties of molybdenum-niobium single crystals is characterized in that the heating rate of the vacuum annealing in step 2 is 20°C / min to 40°C / min. The present invention can ensure uniform heating of the sample and avoid oxidation during the heating process caused by too slow a heating rate by controlling the heating rate.
[0016] The above method for improving the room temperature mechanical properties of molybdenum-niobium single crystals is characterized in that the vacuum annealing time in step 2 is 110 minutes to 130 minutes. The present invention can control the annealing time to ensure that the sample obtains a uniform structure at the temperature and avoid severe oxidation of the sample in a high temperature environment.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] 1. The present invention effectively improves the strength and high-temperature stability of pure molybdenum single crystals by adding niobium as an alloy element to molybdenum single crystals, and vacuum anneals the molybdenum-niobium single crystals prepared by electron beam suspension zone melting, effectively reducing the internal stress of the molybdenum-niobium single crystal system, thereby promoting dislocation slip, thereby improving the mechanical properties of the molybdenum-niobium single crystals, especially the plastic deformation ability.
[0019] 2. The annealing process proposed by the method of the present invention is simple and easy to operate, which can provide a possibility for improving the room temperature mechanical properties of the molybdenum-niobium alloy single crystal. Through the vacuum annealing process under different conditions, the defect control in the molybdenum-niobium alloy single crystal can be achieved, and the room temperature mechanical properties of the molybdenum-niobium alloy single crystal can be effectively improved.
[0020] 3. The present invention improves the room temperature mechanical properties of the Mo-Nb alloy single crystal by controlling the temperature of vacuum annealing. 97 Nb 3For single crystal, annealing at 1285℃~1315℃ greatly improves the elongation of the alloy, but greatly reduces the yield strength. 97 Nb 3 The optimal annealing temperature for single crystal is 1485℃~1515℃. 94 Nb 6 For single crystal, low temperature annealing at 1085℃~1115℃ and 1285℃~1315℃ can significantly improve the yield strength of the alloy. Annealing at higher temperatures of 1485℃~1515℃ and 1685℃~1715℃ can effectively improve the elongation of the alloy. 94 Nb 6 The optimal annealing temperature for single crystal is 1285℃~1315℃.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 1 of the present invention.
[0023] Figure 2 This is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties before annealing prepared in step 2 of Example 1 of the present invention.
[0024] Figure 3 This is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties before annealing prepared in step 2 of Example 4 of the present invention.
[0025] Figure 4 This is a metallographic image of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 4 of the present invention.
[0026] Figure 5 This is a metallographic image of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 4 of the present invention.
[0027] Figure 6 This is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 5 of the present invention.
[0028] Figure 7 This is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 5 of the present invention.
[0029] Figure 8 This is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 8 of the present invention.
[0030] Fig. 9This is a metallographic image of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 8 of the present invention.
[0031] Fig.10 This is a metallographic image of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 8 of the present invention.
[0032] Fig.11 These are the room temperature tensile properties test results of the single crystal molybdenum-niobium alloys with improved mechanical properties prepared in Examples 1 to 4 of the present invention.
[0033] Fig.12 These are the room temperature tensile properties test results of the single crystal molybdenum-niobium alloys with improved mechanical properties prepared in Examples 5 to 8 of the present invention. DETAILED DESCRIPTION
[0034] Example 1
[0035] This embodiment includes the following steps:
[0036] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 30 mm and a length of 100 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 3%, and the balance is molybdenum, and the molecular formula is Mo 97 Nb 3 ;
[0037] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1085°C to 1115°C; the vacuum annealing heating rate is 30°C / min; the vacuum annealing time is 120min;
[0038] Step 3: The single crystal molybdenum-niobium alloy before annealing and the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 are machined into tensile specimens, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile property test is 3 mm / min.
[0039] According to tests, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 408.5 MPa, and the elongation is 9.53%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 380 MPa, and the elongation is about 10.1%.
[0040] Example 2
[0041] This embodiment includes the following steps:
[0042] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 29 mm and a length of 98 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 3%, and the balance is molybdenum, and the molecular formula is Mo 97 Nb 3 ;
[0043] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1285°C to 1315°C; the vacuum annealing heating rate is 20°C / min; the vacuum annealing time is 110min;
[0044] Step 3: The single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 is machined into a tensile specimen, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile performance test is 3 mm / min.
[0045] According to tests, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 382 MPa, and the elongation is 15.45%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 380 MPa, and the elongation is about 10.1%.
[0046] Example 3
[0047] This embodiment includes the following steps:
[0048] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 31 mm and a length of 102 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 3%, and the balance is molybdenum, and the molecular formula is Mo 97 Nb 3 ;
[0049] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1485°C to 1515°C; the vacuum annealing heating rate is 40°C / min; the vacuum annealing time is 130min;
[0050] Step 3: The single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 is machined into a tensile specimen, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile performance test is 3 mm / min.
[0051] According to tests, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 403 MPa, and the elongation is 13.17%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 380 MPa, and the elongation is about 10.1%.
[0052] Example 4
[0053] This embodiment includes the following steps:
[0054] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 30 mm and a length of 101 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 3%, and the balance is molybdenum, and the molecular formula is Mo 97 Nb 3 ;
[0055] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1685°C to 1715°C; the vacuum annealing heating rate is 30°C / min; the vacuum annealing time is 115min;
[0056] Step 3: The single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 is machined into a tensile specimen, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile performance test is 3 mm / min.
[0057] After testing, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 400.3 MPa, and the elongation is 12.7%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 380 MPa, and the elongation is about 10.1%.
[0058] Figure 1 is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 1 of the present invention, Figure 2 is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 1 of the present invention, Figure 3 The X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 4 of the present invention is as follows: Figure 1-Figure 3 It can be seen that the single crystal Mo-Nb alloy before and after annealing only has a peak at 2θ of 116.1°, which represents the diffraction of the 222 crystal plane. This result shows that despite the high temperature annealing at 1700°C, the single crystal Mo-Nb alloy maintains a single crystal structure.
[0059] Figure 4 is a metallographic image of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 4 of the present invention, Figure 5 This is a metallographic image of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 4 of the present invention. Figure 4 and Figure 5 It can be seen that the number of subgrain boundaries in the single crystal Mo-Nb alloy with improved mechanical properties is significantly reduced compared with the single crystal Mo-Nb alloy before annealing, which means that the number of defects in the single crystal Mo-Nb alloy is greatly reduced after annealing, and the performance is improved.
[0060] Fig.11 The room temperature tensile properties test results of the single crystal molybdenum-niobium alloys with improved mechanical properties prepared in Examples 1 to 4 of the present invention are as follows: Fig.11 It can be seen that after low temperature annealing at 1085℃~1115℃, Mo 97 Nb 3 The yield strength and elongation both increased slightly. After annealing at 1285℃~1315℃, Mo 97 Nb 3 The elongation of Mo increases significantly. When the annealing temperature is further increased to 1485℃~1515℃ and 1685℃~1715℃, 97 Nb 3 The yield strength and elongation of the single crystal are not much different from those before annealing. Therefore, in order to obtain Mo with higher elongation 97 Nb 3 For single crystal samples, 1285℃~1315℃ is the best vacuum annealing temperature.
[0061] Example 5
[0062] This embodiment includes the following steps:
[0063] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 30 mm and a length of 99 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 6%, and the balance is molybdenum, and the molecular formula is Mo 94 Nb 6 ;
[0064] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1085°C to 1115°C; the vacuum annealing heating rate is 20°C / min; the vacuum annealing time is 125min;
[0065] Step 3: The single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 is machined into a tensile specimen, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile performance test is 3 mm / min.
[0066] After testing, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 474.7 MPa, and the elongation is 9.8%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 431 MPa, and the elongation is about 10.3%.
[0067] Example 6
[0068] This embodiment includes the following steps:
[0069] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 29 mm and a length of 102 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 6%, and the balance is molybdenum, and the molecular formula is Mo 94 Nb 6 ;
[0070] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1285°C to 1315°C; the vacuum annealing heating rate is 40°C / min; the vacuum annealing time is 120min;
[0071] Step 3: The single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 is machined into a tensile specimen, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile performance test is 3 mm / min.
[0072] After testing, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 470.3 MPa, and the elongation is 11.8%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 431 MPa, and the elongation is about 10.3%.
[0073] Example 7
[0074] This embodiment includes the following steps:
[0075] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 31 mm and a length of 98 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 6%, and the balance is molybdenum, and the molecular formula is Mo 94 Nb 6 ;
[0076] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1485°C to 1515°C; the vacuum annealing heating rate is 30°C / min; the vacuum annealing time is 110min;
[0077] Step 3: The single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 is machined into a tensile specimen, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile performance test is 3 mm / min.
[0078] After testing, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 439.3 MPa, and the elongation is 16%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 431 MPa, and the elongation is about 10.3%.
[0079] Example 8
[0080] This embodiment includes the following steps:
[0081] Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 30 mm and a length of 100 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 6%, and the balance is molybdenum, and the molecular formula is Mo 94 Nb 6 ;
[0082] Step 2: The single crystal molybdenum-niobium alloy obtained in step 1 before annealing is placed in a vacuum of no more than 5×10 -3 Pa, vacuum annealing is performed to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; the vacuum annealing temperature is 1685°C to 1715°C; the vacuum annealing heating rate is 30°C / min; the vacuum annealing time is 130min;
[0083] Step 3: The single crystal molybdenum-niobium alloy with improved mechanical properties obtained in step 2 is machined into a tensile specimen, and then the tensile properties are tested at room temperature to obtain the yield strength and elongation; the diameter of the tensile specimen is 3 mm, and the length of the gauge section is 30 mm; the tensile speed during the tensile performance test is 3 mm / min.
[0084] After testing, the yield strength of the single crystal molybdenum-niobium alloy with improved mechanical properties obtained in this embodiment is 425.5 MPa, and the elongation is 16.95%. The yield strength of the single crystal molybdenum-niobium alloy before annealing is 431 MPa, and the elongation is about 10.3%.
[0085] Figure 6 is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 5 of the present invention, Figure 7 is an X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 5 of the present invention, Figure 8 The X-ray diffraction pattern of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 8 of the present invention is shown in FIG. Figure 6-Figure 8 It can be seen that the single crystal Mo-Nb alloy before and after annealing only has a peak at 2θ of 116.1°, which represents the diffraction of the 222 crystal plane. This result shows that despite the high temperature annealing at 1700°C, the single crystal Mo-Nb alloy maintains a single crystal structure.
[0086] Fig. 9 is a metallographic image of the single crystal molybdenum-niobium alloy before annealing prepared in step 1 of Example 8 of the present invention, Fig.10 This is a metallographic image of the single crystal molybdenum-niobium alloy with improved mechanical properties prepared in step 2 of Example 8 of the present invention. Fig. 9 and Fig.10 It can be seen that the number of subgrain boundaries in the single crystal Mo-Nb alloy with improved mechanical properties is significantly reduced compared with the single crystal Mo-Nb alloy before annealing, which means that the number of defects in the single crystal Mo-Nb alloy is greatly reduced after annealing, and the performance is improved.
[0087] Fig.12 The room temperature tensile properties test results of the single crystal molybdenum-niobium alloys with improved mechanical properties prepared in Examples 5 to 8 of the present invention are as follows: Fig.12 It can be seen that for Mo 94 Nb 6The strength of the single crystal increases after annealing, and this upward trend decreases with the increase of annealing temperature. The maximum value appears after annealing at 1085℃~1115℃. The elongation shows a slight decrease after annealing at 1085℃~1115℃ and 1285℃~1315℃, and a significant increase after annealing at 1485℃~1515℃ and 1685℃~1715℃. By comprehensive comparison with Mo 94 Nb 6 The optimal annealing temperature for single crystal is 1285℃~1315℃.
[0088] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for improving the room temperature mechanical properties of molybdenum-niobium single crystals, characterized in that: The method comprises the following steps: Step 1: Mix a molybdenum raw material and a niobium raw material, and then perform electron beam suspension zone melting to obtain a single crystal molybdenum-niobium alloy before annealing; the single crystal molybdenum-niobium alloy is a rod-shaped sample with a diameter of 29 mm to 31 mm and a length of 98 mm to 102 mm, and the crystal orientation segregation angle of the single crystal molybdenum-niobium alloy is not greater than 3 degrees; the mass content of niobium element in the single crystal molybdenum-niobium alloy is 3%, and the balance is molybdenum, and the molecular formula is Mo 97 Nb3; or the mass content of niobium in the single crystal molybdenum-niobium alloy is 6%, the balance is molybdenum, and the molecular formula is Mo 94 Nb6; Step 2: vacuum annealing the single crystal molybdenum-niobium alloy before annealing obtained in step 1 to obtain a single crystal molybdenum-niobium alloy with improved mechanical properties; when the molecular formula of the single crystal molybdenum-niobium alloy is Mo 97 Nb3 annealing temperature is 1485℃~1515℃. When the molecular formula of single crystal molybdenum-niobium alloy is Mo 94 For Nb6, the annealing temperature is 1285℃~1315℃.
2. A method for improving the room temperature mechanical properties of molybdenum-niobium single crystal according to claim 1, characterized in that: The heating rate of the vacuum annealing in step 2 is 20°C / min~40°C / min.
3. The method for improving the room temperature mechanical properties of molybdenum-niobium single crystal according to claim 1, characterized in that: The vacuum annealing time in step 2 is 110 min to 130 min.